Persistent inequities in maternal mortality in Latin America and the Caribbean, 1990-2019 - Rocío Sáenz; Gustavo Nigenda; Ingrid Gómez-Duarte; Karol Rojas; Arachu Castro; Edson Serván-Mori (BMC, 2024)
Abstract Background Despite the resources and personnel mobilized in Latin America and the Caribbean to reduce the maternal mortality ratio (MMR, maternal deaths per 100 000 live births) in women aged 10-54 years by 75% between 2000 and 2015, the region failed to meet the Millenium Development Goals (MDGs) due to persistent barriers to access quality reproductive, maternal, and neonatal health services. Methods Using 1990-2019 data from the Global Burden of Disease project, we carried out a two-stepwise analysis to (a) identify the differences in the MMR temporal patterns and (b) assess its relationship with selected indicators: government health expenditure (GHE), the GHE as percentage of gross domestic product (GDP), the availability of human resources for health (HRH), the coverage of effective interventions to reduce maternal mortality, and the level of economic development of each country. Findings In the descriptive analysis, we observed a heterogeneous overall reduction of MMR in the region between 1990 and 2019 and heterogeneous overall increases in the GHE, GHE/GDP, and HRH availability. The correlation analysis showed a close, negative, and dependent association of the economic development level between the MMR and GHE per capita, the percentage of GHE to GDP, the availability of HRH, and the coverage of SBA. We observed the lowest MMRs when GHE as a percentage of GDP was close to 3% or about US$400 GHE per capita, HRH availability of 6 doctors, nurses, and midwives per 1,000 inhabitants, and skilled birth attendance levels above 90%. Conclusions Within the framework of the Sustainable Development Goals (SDGs) agenda, health policies aimed at the effective reduction of maternal mortality should consider allocating more resources as a necessary but not sufficient condition to achieve the goals and should prioritize the implementation of new forms of care with a gender and rights approach, as well as strengthening actions focused on vulnerable groups.